Risk factor of pressure ulcer among surgical patient at Hospital Universiti Sains Malaysia - Ibrahim, Norulhuda (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2021)
Pressure ulcer are tissues and skin in a wound condition caused by exposure to excessive pressure on the surface of the skin. Pressure ulcer occurs when excessive pressure for more than two to three hours causes disruption of blood flow to the tissues and skin eventually causing the skin and tissues ischemic. Pressure ulcer will start to occur starting with redness and if left untreated the wound will form over time will become large involving tissues, muscles and bones and prone to bacterial infections. The objective this study is to identify the risk factor of pressure ulcer among surgical patient in Hospital USM. The study involved 150 respondents through systematic random sampling. Self -questionnaires were used for data collection from February 2021 to March 2021. The mean age of the respondents was 51.6 ± years, with ages ranging from 18 to 90 years. The results showed that 84(56%) of the respondents were at risk of getting pressure sores, while 25(16.7%) of them had had pressure sores. There were two significant sociodemographic associations between getting stress sores among surgical patients with chronic disease type (p = 0.032) and BMI (p = 0.037). Pressure ulcer risk factors from the ‘Braden Scale’ evidence have shown that all six evidence correlations are significant between pressure ulcer risk prediction and sensory perception (p = 0.000), skin moisture (p = 0.000), nutritional status (p = 0.000), mobility (p = 0.000), activity (p = 0.000), as well as friction and shear (p = 0.000). In conclusion all these risk factors can be prevented through health education by nurses to patients identified as at risk. Preventive measures should also be taken with early treatment and intervention to prevent the occurrence of stress sores which can interfere with quality of life and can be prone to various other complications.